Evaluation of eating habits in a group of children affected by recurrent chalazion - Maioli, Claudio; Marzenta, Sara; Antonacci, Federica; Maioli, Mary; Cioni, Federico; Autelitano, Alessandro (Progress in Nutrition, 2024)
Introduction and purpose: Chalazion is a frequent ocular pathology even in paediatric age. This pathology may be correlated with incorrect eating habits, particularly with excessive consumption of saturated fats and simple sugars. The present work aimed to evaluate a possible correlation of eating habits with the manifestation of the pathology in a group of paediatric subjects with recurrent chalazion. Materials and methods: In 29 children aged between 1 and 14 years with recurrent chalazion, their eating habits were analysed using a detailed and specially prepared questionnaire. Results: excessive consumption of sausages, sugary drinks, and sweets and low fish consumption. However, the consumption of fruit and vegetables and complex carbohydrates is normal.